Design and implementation of cybersecurity testbed for industrial IoT systems - Lee, Seokcheol; Lee, Seokjun; Yoo, Hyunguk; Kwon, Sungmoon; Shon, Taeshik (Journal of Supercomputing, 2018)
In the era of Industry 4.0, information and communication technology (ICT) has been applied to various critical infrastructures, such as power plants, smart factories, and financial networks, to ensure and automate industrial systems. In particular, in the field of power control systems, ICT technology such as industrial internet of things (IoT) is applied for efficient remote measurement. Therefore, legacy systems that were previously operated as standalone now have contact points with the external networks. In this trend, security vulnerabilities from legacy ICT have been inherited by power control systems. Therefore, various security technologies are being researched and developed to cope with cyber vulnerabilities and threats. However, it is risky to apply novel security technologies that are not verified as secure, to power control systems, the availability of which must be guaranteed to provide electricity consistently. Thus, verifying the effectiveness and stability of new security technologies is necessary to apply the technologies to power control systems. In this paper, we analyze the configuration and characteristics of the power control systems network, which is an area where industrial IoT technology is applied. We also build a testbed environment that can verify the security technology and conduct experiments to confirm the security technology for the power control system and the suitability of the testbed. The proposed testbed will be able to stably incorporate new security technologies into the critical industrial infrastructure. Further, it is also expected that the security and stability of the system will be enhanced.
Keywords: Cyber vulnerabilities; Design and implementations; Industrial control systems; Industrial infrastructure; Information and Communication Technologies; Intrusion Detection Systems; Security and stability; Security vulnerabilities; Industrial control system; Intrusion detection system; Testbed